Increased 25-hydroxycholesterol as an indicator for patients with vestibular neuritis - Song, Xuhua; Liang, Jingwei; Tian, Congzhe (Frontiers in Neurology, 2025)
BackgroundVestibular neuritis (VN) is one of the most common diseases in vestibular vertigo. 25-hydroxycholesterol (25-HC) was correlated to neuroinflammation, however, whether the level of serum 25-HC could be used to diagnose the VN occurrence remains unclear.MethodsThe enrolled patients were divided into VN and healthy control groups. Afterwards, the potential risk factors were assessed in these two groups. Subsequently, the complete blood count was performed upon hospital admission.ResultsThe serum 25-HC and C-reactive protein (CRP) were detected in two groups using liquid chromatography-mass spectrometry and a high-sensitive immunonephelometric assay. Moreover, the correlation of 25-HC to inflammatory factors was analyzed. Finally, the receiver operating characteristic curve analysis was performed to predict the diagnosis effect of 25-HC in VN occurrence. The age, gender, BMI, living habits, disease history, and cholesterol did not affect the VN occurrence. However, 25-HC was dramatically increased in VN patients, meanwhile, peripheral blood leukocyte and neutrophil/lymphocyte ratio were also elevated in VN patients. Importantly, 25-HC was positively correlated to CRP and leukocytes. Additionally, the level of serum 25-HC could be used to predict the VN occurrence.ConclusionSerum 25-HC may diagnose the occurrence of VN.